The Senior High School Student-Mothers in the New Normal: Understanding their Lived Experiences on Modular Distance Learning - Aceret, Dan Manayon T.; Delos Reyes, Mitch Joe V.; Ocampo, Anna Vanessa; Valencia, Mark Janree L. (Future Science / FSH-PH Publications, 2022)
Balancing motherhood and academic life are a difficult task - being a mother is a demanding role, and being a student is also demanding. With the advent of the new learning modality, specifically modular distance learning, SHS student-mothers face a whole new circumstance in addition to their existing dual roles. This case study explored the lived experiences of five senior high school student mothers in the modular distance learning. Participants met the inclusion criteria of a student mother, which includes (1) a student-mother under the General Academic Strand in a Public Stand-alone Senior High School of the School of the Schools Division of the City of Batac; (2) a working student mother and living with her child; and (3) willingness to participate in the study. Four major themes emerged in the participants' lived experiences, which include (1) struggles with dual roles, (2) learning challenges, (3) realizations, and (4) a strong support system. The findings revealed that the participants faced adversities and struggles as mothers and students and remained more steadfast and resilient in fulfilling their dreams of finishing their senior high school and receiving a basic education diploma amid the pandemic. Hence, the lived experiences of student mothers have established baseline data for developing educational programs and guidance services that can meet the needs of student mothers amid the pandemic.